A novel biflavone from Reineckia carnea induces apoptosis of human renal cancer 786-O cells - Jianqiong Yang; Bang Xiao; Bang Xiao; Yamei Li; Yamei Li; Xiaoxuan Liu; Xiaoxuan Liu; Minhong Zhang; Yaoling Luo; Biao Wang; Hai Liu; Hai Liu (Frontiers Media S.A., 2022)
Renal cell carcinoma (RCC) is a common malignant tumor of the urinary system, which is highly invasive, metastatic, and insensitive to radiotherapy and chemotherapy. Chinese herbal medicine has always been an important source of anti-tumor drug development. Reineckia carnea Kunth is a traditional herb commonly used by the Miao nationality in southwest China. In this study, the extract of Reineckia carnea was isolated and purified by reverse phase preparative chromatography and other chromatographic techniques. According to the physicochemical properties and spectral data, the structure of the compound was identified, and a novel biflavone compound named Reineckia-biflavone A (RFA) was obtained. The result of antiproliferative activity showed that RFA had cytotoxicity on 786-O cells with an IC50 value of 19.34 μmol/L. The results of CCK-8 and hemolysis assays showed that RFA was not significantly cytotoxic to both red blood cells (RBC) and peripheral blood mononuclear cells (PBMC). By Hoechst 33258 apoptosis staining, typical apoptotic morphology was observed under fluorescence microscope. RFA could induce the apoptosis of 786-O cells with the increase of apoptosis rate. The cell cycle tests showed that the cell proportion was obviously arrested in the S phase. At the same time, RFA could decrease the mitochondrial membrane potential and increase the intracellular free Ca2+ concentration. Western blot showed that the expression levels of pro-apoptotic proteins (Bax, Caspase-3, Cleaved Caspase-3, and Cytochrome c) in cells rose, while the expression level of anti-apoptotic proteins (Bcl-2) declined significantly. In conclusion, this study suggests that the RFA is a new biflavone determined by SciFinder retrieval. The apoptosis may be triggered by RFA through the mitochondrial pathway, which is mediated by up-regulating the intracellular calcium ion, down-regulating the mitochondrial membrane potential, and changing the apoptosis-related proteins.